A study of cooperative advertising in a one-manufacturer two-retailer supply chain based on the multi-stage dynamic game theory. (2018) - Zhang, Hong; Zhang, Quan-ju
In this paper, the coordination of cooperative advertising decisions is analysed in a supply chain with one manufacturer and two retailers. Suppose the manufacturer invests in national advertising and one retailer invests in local advertising, the manufacturer agrees to share part of the local advertising cost with the retailer. Meanwhile, the other retailer refuses to take part in cooperative advertising. The manufacturer and retailer who put investment in cooperative advertising could choose cooperative or non-cooperative attitude, but the other retailer always chooses non-cooperative attitude. We select four decision variables including local advertising effort, two retailers' marginal profits, and price of product to discuss seven three-stage dynamic game models according to the parties' attitudes being cooperative or not. Seven game models, including one non-cooperative model, five partial cooperative models and one cooperative model, are investigated in detail based on a whole mathematical analysis. By comparing the proposed seven models, several interesting propositions are obtained and the corresponding interesting results are also acquired via these propositions.